"I'm Healthy, It's Not Going To Be Me": Exploring experiences of carriers identified through a population reproductive genetic carrier screening panel in Australia. Issue 8 (6th May 2016) - Beard, Catherine A.; Amor, David J.; Di Pietro, Louisa; Archibald, Alison D.
Abstract : Advancing genetic testing technologies mean that population‐based carrier screening for multiple inherited conditions is now available. As the number of genetic conditions being screened increases, there is a need for research into how people experience these screening programs. This research aimed to explore how women experience simultaneous carrier screening for three inherited conditions: cystic fibrosis (CF), spinal muscular atrophy (SMA), and fragile X syndrome (FXS). A qualitative approach was adopted using in‐depth semi‐structured interviews to explore the experiences of ten female participants: five SMA carriers, three CF carriers, and two FXS premutation carriers. Eight participants were pregnant when offered screening by their general practitioner or obstetrician and the decision to have screening was described as straightforward. Participants reported experiencing emotional responses such as anxiety and stress while waiting for either their partner's carrier screen result (CF or SMA carriers) or the pregnancy's CVS result (FXS carrier) and sought additional information about the relevant condition during this time. Most participants were in favor of population carrier screening for these conditions, preferably prior to conception. Genetic counselors played an essential role in supporting couples after they received a carrier result given the variable consent processes undertaken when screening was offered. Further research should focus on the development of reliable online information tailored to people receiving carrier results and strategies for raising awareness of the availability of population carrier screening within the community. © 2016 Wiley Periodicals, Inc.